Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.jnatprod.7b00887
|View full text |Cite
|
Sign up to set email alerts
|

Capsicodendrin from Cinnamosma fragrans Exhibits Antiproliferative and Cytotoxic Activity in Human Leukemia Cells: Modulation by Glutathione

Abstract: Capsicodendrin (CPCD, 1), an epimeric mixture of a dimeric drimane-type sesquiterpene, is one of the major compounds present in the three endemic species of Madagascan traditional chemopreventive plants: Cinnamosma species ( C. fragrans, C. macrocarpa, and C. madagascariensis). Despite the popular use of Cinnamosma in Madagascan traditional medicine and the reported antiproliferative properties of CPCD, elucidation of its mechanism(s) of action is still to be accomplished. In the present study, CPCD at low mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
2
9
0
Order By: Relevance
“…Previously, we demonstrated that the weakly-bioactive dimer 7 dissociated into highly bioactive monomers of 1, and the presence of DMSO enhanced this dissociation [45]. Consistent with the previous study, we found that 7 was significantly more larvicidal when its stock solution was prepared in DMSO vs. acetone, suggesting 7 is a pro-insecticide that requires dissociation into 1 before becoming toxic.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previously, we demonstrated that the weakly-bioactive dimer 7 dissociated into highly bioactive monomers of 1, and the presence of DMSO enhanced this dissociation [45]. Consistent with the previous study, we found that 7 was significantly more larvicidal when its stock solution was prepared in DMSO vs. acetone, suggesting 7 is a pro-insecticide that requires dissociation into 1 before becoming toxic.…”
Section: Discussionsupporting
confidence: 90%
“…In larvae (Figure 3D), at the screening concentration (100 µM), WARB ( 10 ), CDIAL ( 1 ), and CFRAG ( 2 ) were among the most toxic, while POLYG ( 9 ) and CPCD ( 7 ) were moderately efficacious; CML ( 4 ), UGAN ( 5 ), CMOS ( 3 ), DRIM ( 6 ), and CFGL ( 8 ) were among the least toxic. Previously, we found that 7 dissociated into monomers of 1 in DMSO [45]. Thus, in a parallel experiment, we directly compared the larvicidal efficacy of 7 when dissolved as a stock solution in acetone vs. DMSO.…”
Section: Resultsmentioning
confidence: 99%
“…As such, when CPCD was dissolved in DMSO, it displayed similar inhibition as CDIAL. On the other hand, when CPCD was dissolved in acetone, it lacked effects on crop contractions, which confirms our earlier findings that CPCD has limited bioactivity in its dimeric form (Inocente et al, 2019;Karmahapatra et al, 2018). The strong inhibition of crop contractions by the dialdehydes CDIAL, POLYG and WARB, but not lactone derivatives with similar structures (CMOS, CML, and DRIM), indicate that electrophilic aldehydes are important in the bioactivity of drimane sesquiterpenes against mosquito visceral muscle.…”
Section: Discussionsupporting
confidence: 86%
“…In addition to CDIAL, other natural drimane sesquiterpenes inhibited the spontaneous contractions of the crop, including CPCD, POLYG, and WARB. CPCD is a dimeric form of CDIAL that rapidly converts into CDIAL monomers in the presence of DMSO (Karmahapatra et al, 2018). As such, when CPCD was dissolved in DMSO, it displayed similar inhibition as CDIAL.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, Harinantenaina and Takaoka also revealed that capsicodendrin ( 3 ) is a mixture of C12′-epimers of cinnamodial-based hemiacetal dimer and not a tetramer of cinnamodial ( 1 ), as proposed in its original isolation report . Importantly, biological activity studies of capsicodendrin ( 3 ) revealed that it exhibits antiproliferative and cytotoxic activity in human leukemia cells . Notable angiogenesis inhibition by capsicodendrin ( 3 ) was also reported .…”
mentioning
confidence: 99%